1988
DOI: 10.1002/bit.260310908
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic acidogenesis of a complex wastewater: I. The influence of operational parameters on reactor performance

Abstract: The influence of operational, parameters, such as hydraulic retention time, organic loading rate, influent substrate concentration, pH, and temperature, on the performance of the first phase of anaerobic digestion has been investigated. A complex substrate based on beef extract was used, and six series of experimental runs were conducted, each one showing the effect of one operational variable. The predominant fermentation products were always acetic and propionic acid, independent of the values of the operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
3
7

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(79 citation statements)
references
References 18 publications
1
68
3
7
Order By: Relevance
“…The distribution of metabolites formed during H 2 fermentation is often a crucial signal in assessing the efficiency of H 2 -producing cultures. [22][23][24] At initial D of 4.5 days Ϫ1 (days 1-2), VFA concentration was higher than ethanol. Butyrate (45.2-49.7%) and acetate (12.9 -15.4%) were the two major components of VFAs in the first two days, though lactate composition was high on day 1.…”
Section: Methodsmentioning
confidence: 99%
“…The distribution of metabolites formed during H 2 fermentation is often a crucial signal in assessing the efficiency of H 2 -producing cultures. [22][23][24] At initial D of 4.5 days Ϫ1 (days 1-2), VFA concentration was higher than ethanol. Butyrate (45.2-49.7%) and acetate (12.9 -15.4%) were the two major components of VFAs in the first two days, though lactate composition was high on day 1.…”
Section: Methodsmentioning
confidence: 99%
“…The overall performance of an acidogenic reactor can be evaluated using the term 'degree of acidification', which is quantified by comparing the COD equivalent of the acidogenic products, i.e. VFA/alcohols plus hydrogen and methane in the biogas, to the influent COD [7]. Table 2 lists that the degree of acidification decreased with an increase of OLR, from 59.1% at 4 gCOD/l d to 28.2% at 24 gCOD/l d for the mesophilic reactor, and from 60.8% at 4 gCOD/l d to 27.1% at 24 gCOD/l d for the thermophilic reactor.…”
Section: Aqueous Productsmentioning
confidence: 99%
“…Specific VFA/alcohol production rate, defined as the rate of VFA/alcohol production per day per unit amount of VSS in the reactor (g/gVSS d), can also be used to evaluate the VFA/alcohol generating capability of an acidogenic reactor [2,7]. The specific VFA/alcohol production rate, as shown in Table 2 24 gCOD/l d for the thermophilic reactor.…”
Section: Aqueous Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that HRT and substrate concentration caused a shift in the metabolic pathways obvious from the shift in the formation of fermentation products [19,22±24]. Under low HRT values, HBu is the predominant metabolite indicating the presence of clostridia [28]. The low B/Ac ratios experienced at the HRTs of 10 and 12 h hinted at the possible presence of HPr and HBu-degrading acidogens.…”
Section: Microbial and Sludge Yieldmentioning
confidence: 99%